Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.35869/reined.v20i2.4226
|View full text |Cite
|
Sign up to set email alerts
|

El patrimonio inmaterial y el paisaje como recursos didácticos: una investigación acción a través del Camino de Santiago

Abstract: El presente trabajo se enmarca en la línea de investigación de la educación patrimonial desde una perspectiva crítica, centrándose en las potencialidades didácticas del patrimonio cultural inmaterial y el paisaje. Se realiza una investigación acción en profesorado de primaria en formación inicial de la Universidade da Coruña. Los objetivos propuestos son indagar sus representaciones sociales sobre el patrimonio cultural inmaterial y analizar los cambios y continuidades que se producen después de realizar un pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(4 reference statements)
2
1
0
Order By: Relevance
“…The lack of recognition of Galician toponymy is particularly alarming, as only 60.7% of the students considered it part of the cultural heritage, in contrast to the 98.2% who identified the cathedral as heritage. This result is similar to that obtained by Pérez-Guilarte [57] for primary education students, where only 61.5% indicated that toponyms were heritage, compared to 100% for the cathedral. Likewise, Moreno-Vera et al [45] found that 88.4% of the early childhood education students recognised castles, churches, monuments, or buildings as heritage, while 53.8% did not consider traditional agricultural jobs as such.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The lack of recognition of Galician toponymy is particularly alarming, as only 60.7% of the students considered it part of the cultural heritage, in contrast to the 98.2% who identified the cathedral as heritage. This result is similar to that obtained by Pérez-Guilarte [57] for primary education students, where only 61.5% indicated that toponyms were heritage, compared to 100% for the cathedral. Likewise, Moreno-Vera et al [45] found that 88.4% of the early childhood education students recognised castles, churches, monuments, or buildings as heritage, while 53.8% did not consider traditional agricultural jobs as such.…”
Section: Discussionsupporting
confidence: 89%
“…Initially, the students' perceptions were more oriented toward tangible elements of cultural heritage, neglecting the intangible ones. This result confirms the lack of visibility of intangible heritage among the general population [61][62][63], as well as within the educational context [45,47,57].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation